The influence of left-behind experiences on depression in single-parent adolescents: the mediating role of family satisfaction and the moderating effects of exercise frequency - Cen, Wang-Cheng; Liang, Jing; Zhang, Xiao-Han; Yan, Wen-Jing; Qian, Jun (Frontiers in Pediatrics, 2025)
With the rise of rural-to-urban labor migration, the number of left-behind children in single-parent families has increased, raising concerns about their mental health. This study examines the impact of left-behind experiences on depression in single-parent left-behind adolescents, particularly focusing on the mediating role of family satisfaction and the moderating effects of exercise frequency and separation age. Using cross-sectional data from the China Psychological Health Guardian Project (CPHG), which includes 23,523 single-parent left-behind adolescents aged 12–18, we collected data on left-behind experiences, depressive symptoms, family satisfaction, exercise frequency, and separation age through questionnaires. Correlation analysis, multiple regression, and moderated mediation models were employed to test the hypotheses. The findings indicate that left-behind experiences significantly predict depressive symptoms (t = 7.77, p < 0.001), and family satisfaction serves as a significant mediator in this relationship (Indirect effect = 0.261, t = 4.971, p < 0.001). Additionally, exercise frequency moderates the effect of family satisfaction on depression (B = 0.42, t = 3.681, p < 0.001), where higher exercise frequency lessens the negative impact of low family satisfaction on depression. These results highlight the crucial roles of family satisfaction and exercise frequency in reducing depressive symptoms among single-parent left-behind adolescents, suggesting that emotional support and regular exercise can enhance their mental health.